Dermatological aspects of ticks in Australia: An update. (4th January 2023) - Khan, Hina Ali; Oskam, Charlotte; Kumarasinghe, Prasad
Abstract: Ticks are ectoparasites that cause dermatologic reactions directly by their bites and indirectly as vectors of bacterial, protozoal and viral diseases. Consequences vary from minor local reactions to significant systemic sequelae and are therefore of clinical relevance to dermatologists. In this article, Australian ticks of medical importance are reviewed through the lens of dermatology.